Role of FOXO3 Activated by HIV-1 Tat in HIV-Associated Neurocognitive Disorder Neuronal Apoptosis - Dong, Huaqian; Ye, Xiang; Zhong, Li; Xu, Jinhong; Qiu, Jinhua; Wang, Jun; Shao, Yiming; Xing, Huiqin (Frontiers in Neuroscience, 2019)
There are numerous types of pathological changes in human immunodeficiency virus (HIV)-associated neurocognitive disorder (HAND), including apoptosis of neurons. HIV-1 transactivator of transcription (Tat) protein, which is encoded by HIV-1, may promote apoptosis in HAND. Forkhead box O3 (FOXO3) is a multispecific transcription factor that has roles in many biological processes, including cellular apoptosis. The aim of this study was to determine whether FOXO3 is activated by HIV-1 Tat and to investigate its role in neuronal apoptosis in HAND. We employed tissue staining and related molecular biological experimental methods to confirm our hypothesis. The in vivo experimental results demonstrated that the expression of nuclear FOXO3 increased in the apoptotic neurons of the cerebral cortexes of rhesus macaques infected with simian human immunodeficiency virus (SHIV). The in vitro investigation showed that HIV-1 Tat activated FOXO3, causing it to move from the cytoplasm to the nucleus via the c-Jun N-terminal kinase (JNK) signalling pathway in SH-SY5Y cells. Moreover, FOXO3 down-regulated expression of the anti-apoptosis gene B-cell lymphoma 2 (Bcl-2) and up-regulated the expression of the pro-apoptosis gene Bcl-2-like 11 (Bim) after entering the nucleus, eventually causing cellular apoptosis. Finally, reduction of nuclear FOXO3 reversed cellular apoptosis. Our results suggest that HIV-1 Tat induces FOXO3 to translocate from the cytoplasm to the nucleus via the JNK signalling pathway, leading to neuronal apoptosis. Agents targeting FOXO3 may provide approaches for restoring neuronal function in HAND.